Breastfeeding reduces ultra-processed foods and sweetened beverages consumption among children under two years old - Ana Maria Spaniol; Teresa Helena Macedo da Costa; Gisele Ane Bortolini; Muriel Bauermann Gubert (BMC, 2020)
Abstract Background Breastfeeding and adequate complementary feeding are associated with healthy eating habits, prevention of nutritional deficiencies, obesity and non-communicable diseases. Our aim was to identify feeding practices and to evaluate the association between breastmilk intake and complementary feeding, focusing on ultra-processed foods (UPF) and sweetened beverages, among children under 2 years old. Methods We conducted a cross-sectional study including 847 children from 20 Primary Health Units. We evaluated children's food consumption using a food intake markers questionnaire. We conducted a logistic regression to evaluate the effect of breastmilk intake on feeding practices. Results The breastmilk intake was associated with lower odds of consuming non-recommended foods, such as cookies or crackers (OR: 0.29; IC 95%: 0.20-0.41) for children under 6 months, yogurt (OR: 0.33; CI 95%: 0.12-0.88) for children between 6 and 12 months and soft drinks (OR: 0.36; CI 95%: 0.17-0.75) for children between 12 and 24 months. Moreover, the breastmilk intake was associated with lower odds of consuming UPF (OR: 0.26; CI 95%: 0.09-0.74) and sweetened beverages (OR: 0.13; CI 95%: 0.05-0.33) for children under 6 months. For children between 12 and 24 months, breastmilk intake was associated with lower odds of consuming sweetened beverages (OR: 0.40; CI 95%: 0.24-0.65). Conclusion Breastmilk intake was associated with a reduced consumption of UPF and sweetened beverages. Investment in actions to scale up breastfeeding can generate benefits, besides those of breastmilk itself, translating into better feeding habits and preventing health problems in childhood.